Experiences of commissioning services for child and adolescent mental health in England (UK): a qualitative framework analysis - Samuel P Trethewey; Anna Price; Kate Allen; Tamsin Newlove-Delgado; Frances Mathews (BMJ Open)
Objectives To explore commissioners’ experiences of commissioning services for child and adolescent mental health, their perspectives on the needs of their populations, the challenges they face and their needs for support and data.Design Qualitative study involving semi-structured interviews. All interviews were audio-recorded and transcribed verbatim. Data were analysed using framework analysis.Setting England, UK.Participants 12 integrated care board commissioners, responsible for commissioning NHS England Child and Adolescent Mental Health Services (CAMHS).Results We identified five themes: reflections on role; priorities and tensions: working in a complex and evolving integrated care system; insights and evidence: the role and use of data and informants; childrens mental health in the limelight: influences and expectations; and responding to need CAMHS as the answer to everything. Combined, these themes highlight the integral role commissioners play in providing oversight over the local system and challenges to this role including disproportionate funding for services for child and adolescent mental health, different use and value ascribed to qualitative and quantitative data, rises in demand and the limited focus on early intervention and prevention.Conclusions CAMHS commissioners are currently negotiating a complex and changing political, social and economic environment with competing priorities and pressures. Our research indicates that commissioners require greater support as their roles continue to evolve.